Activity Spaces in Interdisciplinary and International Research - Hölzel, David J. (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Since the late 20th century activity spaces have mainly been perceived as a niche concept in German-speaking spatial research. Meanwhile, international research on activity spaces has developed further and gained quite some attention recently. This paper elaborates a comprehensive definition of activity spaces and presents current fields of application with special regard to research on travel behaviour, segregation and public health. Activity spaces as a concept improve estimates of the interactions between individuals and their respective social or built environments. Therefore, insights on activity spaces might ease the development of adequate planning and policy measures. In order to facilitate the systematic generation of future research questions, hypotheses, research designs and practice-oriented insights, this paper presents both a novel analytical concept and established methods for the study of activity spaces. The paper closes with considerations on possible research perspectives that lie beyond the current state of research.
Keywords: Activity Space; Health; Methods; Mobility; Segregation; Time Geography